Indicators for evaluation of research results applied in practice - Tuan, Nguyen Quang (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
There exist still different views between communities of research and management in Vietnam toward the evaluation of a research task which is considered as having been applied in life and production practice. On basis of surveys made among leads of national level research tasks, this paper aims at introducing indicators used for evaluation of the actual status of application of R&D research works in life and production practice. Code: 17121201